A lymphoma patient with Cytomegalovirus retinitis and post‐autologous hematopoietic cell transplantation immune reconstitution uveitis: A case report and review of the literature. Issue 4 (11th May 2019) - Fuller, Risa; Strauss, Danielle; Steinberg, Amir; Rana, Meenakshi; Keyzner, Alla; Dunn, Dallas; Jacobs, Samantha E.
Abstract: Cytomegalovirus (CMV) retinitis in hematologic malignancies in the absence of hematopoietic cell transplant (HCT) is uncommon. We report a case of a 54‐year‐old woman with peripheral T‐cell lymphoma who develops CMV retinitis and subsequently undergoes an autologous HCT, with eventual development of immune reconstitution uveitis. We further reviewed the PubMed literature on CMV retinitis in patients with lymphoma. We describe that CMV retinitis in patients with lymphoma has variable clinical presentations, may occur at any time during the course of the disease and chemotherapy, and is associated with significant morbidity.